PEMBERDAYAAN BERBASIS MASYARAKAT YANG MENGINTEGRASIKAN DESAIN EFISIEN DAN TEKNOLIGI UMKM BATAKO DAN PAVING DI DESA SABA, BLAHBATUH, GIANYAR - Ni Komang Indra Mahayani; Km. Deddy Endra Prasandya; Ni Putu Widya Yuniari (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community empowerment programme aims to enhance the production efficiency, material quality, and market competitiveness of micro-enterprises producing concrete blocks and paving units in Saba Village, Blahbatuh, Gianyar. The initiative was led by Ni Komang Indra Mahayani and supported by an academic team comprising an Architecture lecturer, a Computer Engineering lecturer, and three students from Universitas Warmadewa. The methodological framework involved site observation, spatial diagnostics, needs assessment, architectural reconfiguration of the production layout, integration of sustainable design principles, and digital capacity-building for marketing. The intervention focused on reorganising production zones into a more linear and coherent spatial sequence—encompassing moulding, curing, storage, and packaging—to minimise unnecessary circulation and improve workflow continuity. Sustainable strategies were incorporated through the provision of a waste-processing area enabling material recirculation, enhanced natural ventilation, and the introduction of green pockets to promote environmental comfort. Material performance was evaluated through a compressive strength test to ensure the paving products comply with technical standards required for governmental and private-sector projects. Improvements to occupational safety included dedicated rest facilities, sanitary amenities, clear evacuation routes, and acoustic treatment within high-noise production areas. Additionally, training in e-catalogue development and digital marketing was delivered to expand market reach and support participation in electronic procurement systems. The outcomes demonstrate significant improvements in production efficiency, product reliability, and operational readiness, highlighting the role of architectural intervention and academic collaboration in strengthening the long-term sustainability and resilience of local micro-enterprises.